ANALISIS PENGARUH KESESUAIAN CITRA DIRI, KUALITAS PRODUK DAN IKLAN PRODUK TERHADAP KESUKAAN MEREK TEH SIAP MINUM DALAM KEMASAN (Studi Pada Konsumen Teh Botol Sosro Di Kota Semarang) - Hanu Kurniawan; Mudji Rahardjo (Faculty of Economics and Business Diponegoro University, 2017)
The interesting phenomenon is the standing of “teh Botol Sosro” as a top brand indexpersistently since 2010 - 2013 indicates that there is a very good marketing strategy onbrand. The simplicity and flexibility of “Teh Botol Sosro” are the major factor appliedby the company to remain in the top sale. Another factor is the naturalness of “Teh BotolSosro” which is always preferred and also inportant to attract the consumers. Thisresearch will analyze the new things that may affect the consumers’ favorite brand “TehBotol Sosro”. The variables of the research are self-image, product quality, andadvertising.This research uses accidental sampling method, which is anyone who happened to meetwith the researchers can be sampled if deemed suitable, the sample in this researchis 100people. Data collection is conducted using questionnaires.Population in this research isconsumers of “Teh Botol Sosro” in Semarang.The results of multiple regression is most influential independent variable on thedependent variable is the self- image variable(0,471),followed by quality productvariable (0,335) and the last is advertising variable. The result of t-test prove that all ofthe independent variables(self-image, quality products, and advertising)have a positiveinfluence on the dependent variable that is brand preferencesa bottled tea “Sosro” inSemarang. Based on the consumers’ opinion,the three independent variables consideredimportant when choosing a bottled tea product “sosro” in semarang. And the result ofadjusted R2 is0,503. It means that 50,3 % of quality products can be explained by thevariable self – image, product quality and advertising. While the remaining 49, 7% isinfluenced by other variables not examined in this research.Keywords: self image, quality of product, advertising, brand preference